Analisis Framing Model Robert N. Entman dalam Representasi Politisi Muda Verrell Bramasta di Instagram - Nia Nandar Hidayah; Rosita Nur Azizah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze the political framing strategy employed by Verrell Bramasta through his personal Instagram account during the 2024 Election campaign, utilizing Robert N. Entman's framing model. Social media, particularly Instagram, was selected as it serves as a strategic platform for young politicians to build their image, foster emotional connections, and garner public support. This study adopts a qualitative descriptive method, employing digital documentation techniques on five Instagram posts from @bramastavrl that received the highest interactions during the campaign period. The analysis was conducted using Entman's four framing indicators: defining the problem, diagnosing the cause, making moral judgments, and offering treatment recommendations. This study reveals that: 1) A distinct framing pattern exists on Verrel Bramasta's Instagram account. 2) Overall, the content shared during the campaign period conveys a positive image of Verrel Bramasta as a young politician capable of representing the younger generation in the political arena. 3) Verrel Bramasta effectively utilizes Instagram through captions, photos, videos, and jingles to shape favorable public perceptions and secure political support.